Schooling behavior of Mugil curema (Perciformes: Mugilidae) in an estuary in southeastern Brazil - De Carvalho, Carolina Delgado [UNESP]; Corneta, Carolina Marocco [UNESP]; Uieda, Virginia Sanches [UNESP] (FapUNIFESP (SciELO), 2007)
Schools of mullets, Mugilidae, are abundant in estuaries and shallow marine waters. We report on the schooling behavior of juvenile white mullet, Mugil curema, in the estuary of the Canto da Paciência stream, in Ubatuba, southeastern Brazil. Schools of small fish (15 to 35 mm TL) were composed of a larger number of individuals (up to a hundred individuals), and were found feeding mainly in shallow nearshore waters, whereas schools of larger fish (40 to 100 mm TL) were observed only in deeper waters. Three patterns of swimming were observed for the schools: stationary feeding, slow movement while searching for food, and rapid displacement. The variations observed in school structure and behavior seem to be related to the balance between predation risk and increasing food intake. Copyright © 2007 Sociedade Brasileira de Ictiologia.
Keywords: Coastal river; Juvenile fish; White mullet; Mugil curema; Mugilidae; Perciformes